From all bloods: the birds in amazonian mythology - Chavarría Mendoza, María (2020)
Almost all the etiological myths of the Amazon confirm that birds play a fundamental role in the lives of the first settlers. These are powerful beings that can function in different spaces or ecological niches: the earth, the water and the sky. It was those who collaborated in obtaining the fire, “Pano”, in preserving life after the flood, fertilizing women when there were no men “Harakabut”, and, moreover, in the town that was “Takana”, they are responsible for choosing the future shamans or “Eyamitekua”. There are humans who married birds “Yine”. Thanks to them, the dead are protected so that they can complete their journey to the other world to meet their ancestors. Not only in oral literature birds are the protagonists, but also in the origin and survival of shamanism. Neither the fabric of the “Cushmas” or original clothes, nor the sacred headdresses can survive without the prodigious intervention of the birds. These myths have been analysed from Lévi-Straus to the Brazilian anthropologist Viveiros De Castro.  In summary, this article presents the most widespread roles of birds in the jungle imagination of many Amazonian inhabitants.